Rhodium-catalyzed NH-indole-directed ortho CH coupling of 2-arylindoles with diazo compounds via metal carbene migratory insertion. Issue 16 (18th April 2018) - Guo, Xiemin; Han, Qingshuai; Tang, Ziyuan; Su, Lv; Zhang, Xinyu; Zhang, Xiaofeng; Lin, Shen; Huang, Qiufeng
Graphical abstract: Highlights: Regioselective CH activation. Mild reaction conditions (under air, 60 °C) High functional group tolerability. 28 examples, up to 99% yield. Abstract: A high regioselective rhodium-catalyzed ortho CH coupling of 2-arylindoles with diazo compounds via NH-indole-directed CH bond activation has been developed. The catalytic reaction features mild reaction conditions, broad substrate scope and good functional group tolerability.